Odpowiedzi

Najlepsza Odpowiedź!
2010-01-07T21:53:00+01:00
Zad 5
l² + m² = k²
z² + x² = y²
b² + c² = a²
(CA)² + (BA)² = (BC)²
(PQ)² + (QR)² = (PR)²
(x + 1)²+ (x)² = (y)²
Zad 6
8² + 6² = x²
64 + 36 = x²
x² = 100
x = √100
x= 10

y² + 15² = 17²
y² = 289 - 225
y² = 64
y = √64
y = 8

2² + 6² = z²
z² = 4 + 36
z² = 40
z = √40
z = √4*10
z = 2√10

a² + 4² = (3√2)²
a² = 9 * 2 - 16
a² = 18 - 16
a² = 2
a = √2
a = 1,44

(3√3)² + (2√5)² = b²
9 * 3 + 4 * 5 = b²
b² = 27 + 20
b² = 47
b = √47
b = 6,85

3² + c² = (√13)²
c² = 13 - 9
c² = 4
c = √4
c = 2

Zad 8
(AC)² + (CB)² = (AB)²
6² + 5² = (AB)²
(AB)² = 36 + 25
(AB)² = 61
AB = √61
AB = 7,81

(AC)² + (AB)² = (CB)²
(7,5)² + AB² = (12,5)²
AB² = 156, 25 - 56,25
AB²= 100
AB = √100
AB = 10

(AC)² + (BC)² = (AC)²
AB² + (√11)² = 5²
AB² = 25 - 11
AB² = 14
AB = √14
AB = 3,74

1 5 1